Irregularity of Carotid Plaque Surface Predicts Subsequent Vascular Event: A MRI Study. Issue 1 (15th January 2020) - Li, Jin; Li, Dongye; Yang, Dandan; Hang, Hailun; Wu, Yawei; Yao, Rong; Chen, Xiaoyi; Xu, Yilan; Dai, Wei; Zhou, Dan; Zhao, Xihai
Abstract : Background: The relationship between plaque compositions and irregular plaque surface and its predictive value for vascular events (VEs) are unknown. Purpose: To investigate the relationship between irregular carotid plaque surface and plaque compositional features and its predictive values for future VEs utilizing magnetic resonance (MR) vessel wall imaging. Study Type: Prospective study. Population: In total, 140 patients with cerebrovascular symptoms were recruited. Field Strength/Sequence: 3T, black blood T1 ‐weighted, black blood T2 ‐weighted, 3D time‐of‐flight, magnetization‐prepared rapid acquisition gradient echo (MP‐RAGE), and 3D motion sensitized driven equilibrium rapid gradient echo (MERGE). Assessment: The carotid artery stenosis and maximum wall thickness (Max WT) were measured. The presence/absence of irregular carotid plaque surface, calcification, lipid‐rich necrotic core (LRNC), intraplaque hemorrhage (IPH), and fibrous cap rupture was determined. After baseline examination, all patients were followed‐up for at least 1 year to record the VEs. Statistical Tests: Independent t ‐test, Mann–Whitney U ‐test, Chi‐square, logistic regression, and Cox regression were used. Results: In total, 82 (58.6%) had irregular plaque surfaces. The carotid Max WT, stenosis, and the presence of surface calcification, LRNC and IPH were significantly associated with irregular plaque surface (all P < 0.05). After adjusted for baseline confounding factors, these associations remained statistically significant (all P < 0.05). During the median follow‐up time of 12.1 months, 37 (26.4%) patients had VEs. Univariable Cox regression analysis showed that the irregular carotid plaque surface was significantly associated with subsequent VEs (hazard ratio [HR], 11.02; 95% confidence interval [CI], 2.65–45.85; P = 0.001). After adjusted for baseline and follow‐up confounding factors, this association remained statistically significant (HR, 13.03; 95% CI, 1.71–99.42, P = 0.013). After further adjusted for intracranial stenosis, this association also remained statistically significant (HR, 12.57; 95% CI, 1.63–96.83, P = 0.015). Data Conclusion: The morphology of carotid atherosclerotic plaque surface determined by MR vessel wall imaging, particularly irregular plaque surface, is an independent predictor for subsequent vascular events. Level of Evidence: 1 Technical Efficacy Stage: 5 J. Magn. Reson. Imaging 2020;52:185–194.